2020
DOI: 10.3390/rs12091464
|View full text |Cite
|
Sign up to set email alerts
|

Isolating Anthropogenic Wetland Loss by Concurrently Tracking Inundation and Land Cover Disturbance across the Mid-Atlantic Region, U.S.

Abstract: Global trends in wetland degradation and loss have created an urgency to monitor wetland extent, as well as track the distribution and causes of wetland loss. Satellite imagery can be used to monitor wetlands over time, but few efforts have attempted to distinguish anthropogenic wetland loss from climate-driven variability in wetland extent. We present an approach to concurrently track land cover disturbance and inundation extent across the Mid-Atlantic region, United States, using the Landsat archive in Googl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 73 publications
3
18
0
Order By: Relevance
“…Our extensive assessment of the products also showed that "high confidence" water pixels were the most reliable, while classification errors were common in moderate (Classes 2 and 3) and lower confidence water classes (Class 4), including confusion with urban areas. These errors, along with similar findings in other DSWE investigations (Vanderhoof et al 2020), informed our decisions to focus solely on "high confidence" water pixels (Class 1) for our analyses. The accuracy assessment, based on JRC reference data (Pekel et al 2016), of water presence (Class 1) and water absence (all other classes), suggests that Class 1 pixels mapped in MODIS images do an effective job of identifying surface water patterns mapped in moderately sized (approximately 25 ha) water bodies located in California.…”
Section: Dswe Accuracy For Mapping Water Bodiessupporting
confidence: 72%
See 3 more Smart Citations
“…Our extensive assessment of the products also showed that "high confidence" water pixels were the most reliable, while classification errors were common in moderate (Classes 2 and 3) and lower confidence water classes (Class 4), including confusion with urban areas. These errors, along with similar findings in other DSWE investigations (Vanderhoof et al 2020), informed our decisions to focus solely on "high confidence" water pixels (Class 1) for our analyses. The accuracy assessment, based on JRC reference data (Pekel et al 2016), of water presence (Class 1) and water absence (all other classes), suggests that Class 1 pixels mapped in MODIS images do an effective job of identifying surface water patterns mapped in moderately sized (approximately 25 ha) water bodies located in California.…”
Section: Dswe Accuracy For Mapping Water Bodiessupporting
confidence: 72%
“…Qualitative assessments of the DSWEmod product reveal accuracy characteristics similar to our and previous DSWE classification efforts (see Figure 2d). As confirmed by comparison with a contemporaneous, higher-resolution image (not shown), "high confidence" water (Class 1) matches open water well, while Classes 3 and 4 overlap with a range of other land cover and land use types, such as mixed vegetation and urban, also observed by Vanderhoof et al (2020). Due to concerns about mapping accuracy, we follow and and focus the remainder of our analyses on the ability to capture "high confidence" water pixels.…”
Section: Dswemod Productionmentioning
confidence: 61%
See 2 more Smart Citations
“…Urbanization has becoming a pressing environmental and social issue across the globe, as the outward growth of urban development into former natural and agricultural lands has had lasting impacts on natural ecosystem services. Within the Chesapeake Bay Watershed (CBW) of the Mid-Atlantic United States, for example, the impacts of urbanization on the loss of natural ecosystems like forests and forested wetlands have been palpable, with over 100 km 2 disturbed between 2015 and 2018 (Dahl 2011;Fretwell et al 1996;Homer et al 2020;Johnson and Lichter 2020;Lacher et al 2019;Scanes 2018;Vanderhoof et al 2020). Despite such losses, urban-speci c environmental problems-speci cally, high atmospheric greenhouse gas concentrations-have been addressed in part by prioritizing urban green spaces like urban forests and wetlands (Bae and Ryu 2015;Pulighe et al 2016;Säynäjoki et al 2018;Xue et al 2019).…”
Section: Introductionmentioning
confidence: 99%